Non-Genetic Factors Affecting Production Traits in Murrah Buffaloes - Chakraborty, Dibyendu; Dhaka, S.S. (Journal of Buffalo Science, 2023)
The present investigation was undertaken to estimate the effect of non-genetic factors on different production traits of Murrah buffaloes maintained at Buffalo Research Centre, Chaudhary Charan Singh Haryana Agricultural University, Hisar, India. A total of 1128 lactation records of 326 Murrah buffalo were targeted to explore the effect of non-genetic factors. The production traits considered for the present study were lactation yield (LY), lactation length (LL), 305 days milk yield (305 MY), peak yield (PY), and days to attain peak yield (DAPY). The highest CV (%) was obtained for PY. The overall least squares means were 2118.10 ± 25.54 kg, 296.60 ± 3.23 days, 2053.88 ± 21.80 kg, 11.08 ± 0.08 kg, and 61.72 ± 1.02 days for LY, LL, 305 MY, PY and DAPY, respectively. The period of calving revealed a highly significant (P<0.01) effect on targeted traits except for LL. Animals in the fourth lactation revealed significantly the highest LY and PY. The effect of the season of calving was highly significant (P<0.01) on all the traits under study. Performances of animals calved during summer seasons were excellent for the traits under the present study. The effect of parity was highly significant (P<0.01) for all the traits under study except for DAPY where it was non-significant. The significant effects of different non-genetic factors like period of calving, the season of calving, and parity of animals on different production traits of Murrah buffaloes indicate that adjustment of effect of non-genetic factors is important for accurate and unbiased estimates of genetic parameters and selection of superior animals.